THE URINARY TRACT INFECTION AS A RISK FACTOR FOR PREECLAMPSIA AT THEBELEN HOSPITAL IN TRUJILLO, 2017-2020 - Nieto Polo Barreto, Valeria (2025)
Introduction. Urinary tract infection is common during pregnancy and may be associated with preeclampsia. Objectives. To determine whether urinary tract infection (UTI) is a risk factor for preeclampsia. Methods. An observational, retrospective, analytical case-control study was conducted at Belén Hospital of Trujillo (2017–2020) with 464 pregnant women ≥20 weeks of gestation. Two groups were formed: with preeclampsia (n=116) and without preeclampsia (n=348), in a 1:2 ratio. Documented history of UTI confirmed by urine culture ≥100,000 CFU/mL, systolic blood pressure ≥140 mmHg or diastolic ≥90 mmHg, and proteinuria ≥300 mg/24 h or ≥+1 on dipstick test were recorded. Pregnant women with metabolic diseases, multiple pregnancies, urinary malformations, or prior preeclampsia were excluded. Chi-square test (p<0.05) and logistic regression adjusted for age, parity, educational level, and prenatal care were used to estimate odds ratios (OR) with 95% confidence intervals (CI). Results. The prevalence of UTI was 22.0%, significantly higher among women with preeclampsia (58.6%) than in controls (9.8%) (p<0.001). UTI was independently associated with preeclampsia (OR=6.2; 95% CI: 2.375–16.346; p<0.001). Women with early-onset preeclampsia (<34 weeks) were 3.26 times more likely to have had UTI compared with those with late-onset disease (p=0.001). No significant association was found with age, parity, educational level, or prenatal care after adjustment. Conclusion. UTI during pregnancy is a significant factor associated to preeclampsia, particularly in early-onset cases.